2010
DOI: 10.1038/nnano.2010.132
|View full text |Cite
|
Sign up to set email alerts
|

Roll-to-roll production of 30-inch graphene films for transparent electrodes

Abstract: The outstanding electrical, mechanical and chemical properties of graphene make it attractive for applications in flexible electronics. However, efforts to make transparent conducting films from graphene have been hampered by the lack of efficient methods for the synthesis, transfer and doping of graphene at the scale and quality required for applications. Here, we report the roll-to-roll production and wet-chemical doping of predominantly monolayer 30-inch graphene films grown by chemical vapour deposition on… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

94
4,281
9
29

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7,505 publications
(4,413 citation statements)
references
References 32 publications
94
4,281
9
29
Order By: Relevance
“…CVD‐grown graphene has made great breakthrough in the growth of large‐area graphene 17, 155, 156, 157, 158, 159, 160. Recently, the synthesis of 2DLMs via CVD methods has been illustrated in many reports especially for MoS 2 ,30, 31, 161, 162, 163, 164, 165, 166, 167, 168, 169, 170, 171, 172, 173, 174, 175, 176, 177, 178, 179, 180, 181, 182, 183, 184, 185 which also shows promising applications in electronics and optoelectronics.…”
Section: Preparation Methods and Characterizationsmentioning
confidence: 99%
“…CVD‐grown graphene has made great breakthrough in the growth of large‐area graphene 17, 155, 156, 157, 158, 159, 160. Recently, the synthesis of 2DLMs via CVD methods has been illustrated in many reports especially for MoS 2 ,30, 31, 161, 162, 163, 164, 165, 166, 167, 168, 169, 170, 171, 172, 173, 174, 175, 176, 177, 178, 179, 180, 181, 182, 183, 184, 185 which also shows promising applications in electronics and optoelectronics.…”
Section: Preparation Methods and Characterizationsmentioning
confidence: 99%
“…As the above mentioned, the theoretical value of the sheet resistance of monolayer graphene is very satisfactory. The resistance of graphene synthesized by chemical vapor deposition (CVD), the acknowledged well‐suited method for growing large‐area and high quality graphene, can low to several hundreds of Ω sq –1 on nickel (Ni) and copper (Cu) 7. For the graphene prepared by another common used methods, chemical and thermal methods, the sheet resistance of reduced graphene oxide (rGO) can reduce to ≈640 Ω sq –1 after thermal annealing at 1000 °C 8.…”
Section: Properties and Preparationmentioning
confidence: 99%
“…Kong et al reported 1 to ≈12 graphene layers simultaneously obtained on polycrystalline Ni film via ambient pressure chemical vapor deposition (APCVD) 18. Cu foil with low carbon solubility was also most commonly used to obtain predominantly single‐layer graphene 7, 19. In addition, Ni–molybdenum (Mo) alloy,20 platinum (Pt),21 cobalt (Co)22 also have been designed for large area monolayer graphene.…”
Section: Properties and Preparationmentioning
confidence: 99%
See 2 more Smart Citations